Successful treatment of Svabhava satmya Viparyaya Yakrit Kshaya (Autoimmune liver cirrhosis) : A case study - Panda, Ashok Kumar; Choudhary, Ashok; Hazra, Jayram (International Research Journal of Ayurveda & Yoga, 2020)
Presentation of a case of Auto immune liver disease (AILD) which was treated with Ayurveda principles, logic and also tried to established the Ayurveda terminology for the AILD. Svabhava satmya is the synergetic properties of dosas and dhatus even though the possession of antagonist properties within them and Svabhava satmya viparyaya (Auto immunity) is rare condition where synergetic properties of dosas and dhatus are lost. It cause many organ specific diseases and Yakrit Kshaya(Cirrhosis of liver) is one of them . It is difficult to diagnose without adequate laboratory support. A 57-year women with persistent jaundice, mild ascites, bilateral pedal oedema, with negative viral hepatitis and other metabolic screening is presented. Portal hypertension with Cirrhosis of liver are found in her ultrasound findings before treatment. An extensive interview was conducted with the patient to know the dosh, Prakriti, etc. Herein, a timeline of her diagnosis and treatment are discussed. The patient was prescribed with Agnideepak, srotasodhaka, snigdha ,Mutrala and Rasayana medication and strict diet to treat Svabhava satmya Virparyaya Yakrit Kshaya (Autoimmune liver cirrhosis.Vardhamana Pippali Rasayana is not helpful to this case. But current medication is well tolerated and the midline stiff of liver in fibroscan reduced to 27 Kpa from 57 Kpa. Her Portal hypertension is corrected and Liver parenchyma regenerated. The patient has maintained the normal liver enzymes and her overall health is improved even if the drug regimen was stopped after one year. Her therapeutic regimen was tried conservatively as it was successful, so it may be serving a useful therapeutic model for this type of rare Chronic Liver disease (CLD).